Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

By employing a lithium transition metal composite oxide with tailored composition and structural features as the positive electrode active material, the energy density of nonaqueous electrolyte secondary batteries is significantly improved, addressing the limitations of existing materials.

JP7660286B2Active Publication Date: 2025-04-11PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022503698
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2021-02-25
Publication Date
2025-04-11
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Existing positive electrode active materials for nonaqueous electrolyte secondary batteries face challenges in achieving higher energy density, which is essential for improving battery performance and capacity.

Method used

A lithium transition metal composite oxide with a specific composition and structural properties, including a BET specific surface area of 1-4 m^2/g and an average pore diameter of 100 nm or less, is used as the positive electrode active material. This material has a general formula Li_xMn_yNi_zMe_2-x-y-zO_aF_b, where x, y, z, and b are within specific ranges, and Me includes elements such as Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb.

Benefits of technology

The use of this lithium transition metal composite oxide positive electrode active material enhances the energy density of the battery by optimizing the balance between capacity and active material density, leading to improved battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660286000002
    Figure 0007660286000002
  • Figure 0007660286000001
    Figure 0007660286000001
Patent Text Reader

Abstract

This positive electrode active material for nonaqueous electrolyte secondary batteries contains a lithium transition metal composite oxide. This lithium transition metal composite oxide is represented by general formula LixMnyNizMe2-x-y-zOaFb (wherein 1 ≤ x ≤ 1.2; 0.4 ≤ y ≤ 0.7; 0.1 ≤ z ≤ 0.4; 0 < b ≤ 0.2; 1.9 ≤ a + b ≤ 2.1; and Me represents at least one element selected from among Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P and Sb), while having a BET specific surface area of from 1 m2 / g to 4 m2 / g and an average pore diameter of 100 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the positive electrode active material for a non-aqueous electrolyte secondary battery.

Background Art

[0002] Conventionally, lithium transition metal composite oxides have been widely used as positive electrode active materials for secondary batteries such as lithium ion batteries, and Li-excess type positive electrode active materials containing a large amount of Li have attracted attention for high-output secondary batteries. Further, depending on the application, the characteristics required for the secondary battery are different, and Patent Document 1 discloses a technique for controlling the particle aggregation form of the positive electrode active material to improve the output at low temperature.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of the Invention

[0004] In recent years, higher capacity and higher output have been increasingly demanded for secondary batteries, and further densification of the batteries has been studied. However, the positive electrode containing the positive electrode active material disclosed in Patent Document 1 has room for improvement in terms of improving the energy density.

[0005] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one aspect of the present disclosure contains a lithium transition metal composite oxide. The lithium transition metal composite oxide has the general formula Li x Mn y Ni z Me 2-x-y-z O a F b (where 1 ≦ x ≦ 1.2, 0.4 ≦ y ≦ 0.7, 0.1 ≦ z ≦ 0.4, 0 < b ≦ 0.2, 1.9 ≦ a + b ≦ 2.1, and Me is at least one element selected from Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb), and the BET specific surface area is 1 m2 / g or more 4m 2 / g or less, and the average pore diameter is 100 nm or less.

[0006] A secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above-described positive electrode active material for non-aqueous electrolyte secondary batteries, a negative electrode, and a non-aqueous electrolyte.

[0007] According to the positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, the energy density of the positive electrode can be improved. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a longitudinal sectional view of a cylindrical nonaqueous electrolyte secondary battery as one example of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Li-excessive positive electrode active materials, in which a part of the transition metal layer of a lithium transition metal composite oxide having a layered rock salt structure is replaced with Li, have been attracting attention as materials for high-power secondary batteries. Energy density [Wh / L] is calculated from (capacity [Ah / g]) x (voltage [V]) x (active material density [g / L]), but since capacity and active material density are generally in a trade-off relationship, a positive electrode with high energy density cannot be obtained simply by increasing the active material density. As a result of intensively studying such a problem, the present inventors have found that the energy density of the positive electrode can be improved by making the composition of the lithium transition metal composite oxide contained as the positive electrode active material a Li-excessive system containing a large amount of Mn, while setting the BET specific surface area and the average pore size of the particles within a predetermined range. As a result, the present inventors have come up with the following positive electrode active material for non-aqueous electrolyte secondary batteries, which can improve the energy density of the positive electrode.

[0010] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a lithium transition metal composite oxide. The lithium transition metal composite oxide is represented by the general formula Li x Mn y Ni z Me2-x-y-z O a F b (wherein 1 ≦ x ≦ 1.2, 0.4 ≦ y ≦ 0.7, 0.1 ≦ z ≦ 0.4, 0 < b ≦ 0.2, 1.9 ≦ a + b ≦ 2.1, and Me is at least one element selected from Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb), and the BET specific surface area is 1 m 2 / g or more and 4 m 2 / g or less, and the average pore diameter is 100 nm or less.

[0011] Hereinafter, with reference to the drawings, an example of an embodiment of a cylindrical secondary battery according to the present disclosure will be described in detail. In the following description, specific shapes, materials, numerical values, directions, etc. are examples for facilitating the understanding of the present disclosure, and can be appropriately changed according to the specifications of the cylindrical secondary battery. Further, the exterior body is not limited to a cylindrical shape, and may be, for example, a rectangular shape or the like. Also, in the following description, when a plurality of embodiments and modification examples are included, it is initially assumed that their configurations can be used in appropriate combinations.

[0012] FIG. 1 is an axial cross-sectional view of a cylindrical secondary battery 10 which is an example of an embodiment. In the secondary battery 10 shown in FIG. 1, an electrode body 14 and a non-aqueous electrolyte are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. Hereinafter, for convenience of explanation, the side of the sealing body 16 will be referred to as "upper" and the bottom side of the exterior body 15 will be referred to as "lower".

[0013] The opening end of the exterior body 15 is closed with the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the underside of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 extends through the through hole of the insulating plate 18 to the bottom side of the exterior body 15 and is welded to the inner bottom surface of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal. In addition, when the negative electrode lead 20 is installed at the terminal portion, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner bottom surface of the exterior body 15.

[0014] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the inside of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.

[0015] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk shape or a ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, and as a result, the upper valve body 25 swells toward the cap 26 and separates from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.

[0016] The positive electrode 11, negative electrode 12, separator 13, and non-aqueous electrolyte that constitute the secondary battery 10 will be described in detail below, in particular the positive electrode active material contained in the positive electrode mixture layer that constitutes the positive electrode 11.

[0017] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface layer, or the like can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part where the positive electrode lead 19 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.

[0018] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).

[0019] The positive electrode active material includes a lithium transition metal composite oxide. The lithium transition metal composite oxide preferably has a crystal structure of the O3 structure. For example, from the viewpoint of the stability of the crystal structure, the O3 structure is preferably 50% by volume or more of the crystal structure of the lithium transition metal composite oxide, more preferably 90% by volume or more, even more preferably 98% by volume or more, and particularly preferably 100% by volume. Here, the O3 structure is a layered crystal structure in which lithium is present at the center of an oxygen octahedron, and there are three types of overlapping of oxygen and transition metal per unit lattice, and it belongs to the space group R-3m or C2 / m.

[0020] The lithium transition metal composite oxide has the general formula Li x Mn y Ni z Me 2-x-y-z O a F b (where 1 ≦ x ≦ 1.2, 0.4 ≦ y ≦ 0.7, 0.1 ≦ z ≦ 0.4, 0 < b ≦ 0.2, 1.9 ≦ a + b ≦ 2.1, and Me is at least one element selected from Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb). The molar fraction of each element constituting the lithium transition metal composite oxide can be measured, for example, by inductively coupled plasma (ICP) optical emission spectrometry or ion chromatography (IC) measurement. The positive electrode active material contains the lithium transition metal composite oxide as a main component and may be composed only of the lithium transition metal composite oxide. Note that the positive electrode active material may contain a composite compound other than the lithium transition metal composite oxide as long as the object of the present disclosure is not impaired.

[0021] X, which indicates the proportion of Li in the lithium transition metal composite oxide, satisfies 0.9 ≦ x ≦ 1.2, and preferably satisfies 0.95 ≦ x ≦ 1.05. When x is less than 0.9, the battery capacity may decrease as compared with the case where x satisfies the above range. When x exceeds 1.2, it may lead to a decrease in charge-discharge cycle characteristics as compared with the case where x satisfies the above range.

[0022] Y, which indicates the proportion of Mn to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide, satisfies 0.4 ≦ y ≦ 0.7, preferably satisfies 0.5 ≦ y ≦ 0.7, and more preferably satisfies 0.5 ≦ y ≦ 0.6.

[0023] Z, which indicates the proportion of Ni to the total number of moles of metal elements excluding Li in the lithium transition metal composite oxide, satisfies 0.1 ≦ z ≦ 0.4, preferably satisfies 0.2 ≦ z ≦ 0.4, and more preferably satisfies 0.2 ≦ z ≦ 0.3.

[0024] Me (Me is at least one element selected from Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb) is an optional component with respect to the total molar number of metal elements excluding Li in the lithium transition metal composite oxide, and 2 - x - y - z indicating its ratio satisfies 2 - x - y - z ≥ 0.

[0025] It is preferable that Me does not contain Co. In other words, it is preferable that the lithium transition metal composite oxide does not contain Co. Since Co is expensive, it is preferable to suppress the Co content from the viewpoint of manufacturing cost.

[0026] b indicating the ratio of F in the lithium transition metal composite oxide satisfies 0 < b ≤ 0.2, preferably satisfies 0.02 ≤ b ≤ 0.1, and more preferably satisfies 0.05 ≤ b ≤ 0.1. By containing F in the lithium transition metal composite oxide, the stability of the crystal structure of the lithium transition metal composite oxide is improved. In particular, in a lithium - excess type cathode active material that does not contain Co, the stability of the crystal structure may be low, so the effect of improving the stability by F is remarkable. When the crystal structure of the lithium transition metal composite oxide is stabilized, for example, the durability and safety of the secondary battery are improved.

[0027] The lithium transition metal composite oxide has a BET specific surface area of 1 m 2 / g or more and 4 m 2 / g or less, preferably 3 m 2 / g or more and 4 m 2 / g or less, and an average pore diameter of 100 nm or less, preferably 50 nm or less. When the lithium transition metal composite oxide has the composition of the above general formula and further has a BET specific surface area and an average pore diameter within this range, the energy density of the cathode can be improved. The BET specific surface area can be measured by a commercially available measuring device such as the HM model - 1201 of Macsorb. Also, the average pore diameter can be measured using a mercury porosimeter (for example, AutoPore IV9510 type manufactured by Micromeritics).

[0028] Next, an example of a method for producing a lithium transition metal composite oxide will be described.

[0029] First, while stirring an aqueous solution in which metal salts such as Mn compounds and Ni compounds are dissolved, potassium bicarbonate (KHCO3) or the like is dropped to adjust the pH to the alkaline side, thereby obtaining a transition metal carbonate containing Mn, Ni, or the like by precipitation (co-precipitation). An Me compound may be dissolved in the aqueous solution together with the Mn compound and Ni compound and precipitated. The Mn compound is not particularly limited, but may be, for example, MnSO4, Mn(NO3)2, Mn(CH3COO)2, or the like. The Ni compound is not particularly limited, but may be, for example, NiSO4, Ni(NO3)2, Ni(CH3COO)2, or the like. The Me compound is not particularly limited, but may be, for example, sulfate, nitrate, acetate, or the like of Me.

[0030] The above transition metal carbonate and the Li compound are added and mixed to a predetermined molar ratio, and the resulting mixture is fired to produce a lithium transition metal composite oxide. The firing conditions for the mixture may be a temperature of 700°C to 1000°C and a time of 1 hour to 20 hours, and a multi-stage firing process in which firing is performed in a plurality of temperature ranges may be provided. The firing atmosphere may be an oxygen atmosphere or air. The Li compound is not particularly limited, and may be, for example, LiF, Li2CO3, LiOH, etc. The BET specific surface area and average pore size of the lithium transition metal composite oxide can be changed by adjusting the production method. For example, increasing the firing temperature may reduce the BET specific surface area. In addition, a dispersant may be added to an aqueous solution in which a metal salt is dissolved, thereby adjusting the average pore size of the transition metal carbonate to be precipitated, and changing the average pore size of the lithium transition metal composite oxide. Furthermore, the above lithium transition metal composite oxide may be washed with water, dehydrated, and then heat-treated to evaporate water. The heat treatment conditions are not particularly limited, but the temperature may be 50° C. to 200° C. and the time may be 0.5 to 10 hours.

[0031] As another example of a method for producing a lithium transition metal composite oxide, when a transition metal carbonate containing Mn, Ni, etc. but not Me is added and mixed with a Li compound, a Me compound may be co-added and mixed. In this case, the Me compound is not limited to a compound that dissolves in an aqueous solution, and in addition to Me sulfate, nitrate, acetate, oxide, hydroxide, fluoride, etc. may be used.

[0032] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode, a film with the metal disposed on the surface layer, or the like can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 20 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite layer on both sides of the negative electrode core.

[0033] The negative electrode mixture layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly absorbs and releases lithium ions. Suitable carbon-based active materials are graphites such as natural graphite, such as flake graphite, lump graphite, and earthy graphite, and artificial graphite, such as lump artificial graphite (MAG) and graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material may be a Si-based active material composed of at least one of Si and a Si-containing compound, or a carbon-based active material and a Si-based active material may be used in combination.

[0034] The binder contained in the negative electrode mixture layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode, but it is preferable to use styrene-butadiene rubber (SBR). In addition, it is preferable that the negative electrode mixture layer further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), etc. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, and PAA or a salt thereof.

[0035] [Separator] For example, a porous sheet having ion permeability and insulation is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The separator is preferably made of an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may be a laminate having a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. The separator 13 may also be a multilayer separator including a polyethylene layer and a polypropylene layer, and may have a material such as an aramid resin or ceramic applied to the surface of the separator 13.

[0036] [Non-aqueous electrolyte] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolytic solution), and may be a solid electrolyte using a gel-like polymer or the like. The non-aqueous solvent may be, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, or a mixed solvent of two or more of these. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is substituted with a halogen atom such as fluorine.

[0037] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate, and γ-butyrolactone.

[0038] Examples of the above ethers include cyclic ethers such as 1,3 - dioxolane, 4 - methyl - 1,3 - dioxolane, tetrahydrofuran, 2 - methyltetrahydrofuran, propylene oxide, 1,2 - butylene oxide, 1,3 - dioxane, 1,4 - dioxane, 1,3,5 - trioxane, furan, 2 - methylfuran, 1,8 - cineole, crown ether, etc., and chain - like ethers such as 1,2 - dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o - dimethoxybenzene, 1,2 - diethoxyethane, 1,2 - dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1 - dimethoxymethane, 1,1 - diethoxyethane, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl, etc.

[0039] As the above - mentioned halogen - substituted products, it is preferable to use fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain - like carboxylic acid esters such as fluorinated chain - like carbonates, etc.

[0040] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1 < x < 6, n is 1 or 2), LiB 10 Cl 10 , LiCl, LiBr, LiI, lithium chloroborane, lithium lower aliphatic carboxylate, borate salts such as Li2B4O7, Li(B(C2O4)F2), LiN(SO2CF3)2, LiN(C1F 2l+1SO2)(C m F 2m+1 Examples of the lithium salt include imide salts such as LiPF6, LiPF2, and LiPF6 (where l and m are integers of 1 or more). The lithium salt may be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoints of ion conductivity, electrochemical stability, and the like. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of the solvent.

[0041] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.

[0042] <Example 1> [Synthesis of positive electrode active material] MnSO4 and NiSO4 were dissolved in an aqueous solution with a molar ratio of Mn to Ni of 0.667:0.333, and the solution was reacted for 2.5 hours with stirring. KHCO3 was added dropwise to adjust the pH to 7.5, and the (Mn 0.667 Ni 0.333 )CO3 was precipitated. Next, (Mn 0.667 Ni 0.333 The lithium transition metal composite oxide was obtained by mixing LiF and LiCO3 in a ratio of 0.833:0.05:0.5585 and calcining the mixture in air at 900°C for 10 hours. The composition of the lithium transition metal composite oxide was measured using an ICP emission spectrometer (manufactured by Thermo Fisher Scientific, product name "iCAP6300") and an ion chromatograph (IC) device. The composition was found to be Li 1.167 (M 0.667 Ni 0.333 ) 0.833 O 1.95 F 0.05 The lithium transition metal composite oxide had a BET specific surface area of ​​1.34 m 2 / g and the average pore size was 10.42 nm. This was used as the positive electrode active material of Example 1.

[0043] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a mass ratio of 100:2:2, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode composite slurry. Next, this positive electrode composite slurry was applied to the surface of a positive electrode core made of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to produce a positive electrode in which a positive electrode composite layer was formed on the positive electrode core.

[0044] [Preparation of non-aqueous electrolyte] A non-aqueous solvent was obtained by mixing fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:6. LiPF6 was dissolved in the non-aqueous solvent at a concentration of 1.0 mol / L to obtain a non-aqueous electrolyte.

[0045] [Preparation of test cell] An electrode assembly was prepared by attaching lead wires to the positive electrode and the Li metal counter electrode, and arranging the positive electrode and the counter electrode facing each other with a polyolefin separator interposed therebetween. The electrode assembly and the non-aqueous electrolyte were enclosed in an exterior body made of an aluminum laminate film to prepare a test cell.

[0046] <Example 2> A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the time for reacting MnSO4 and NiSO4 with stirring was changed to 8 hours. The lithium transition metal composite oxide had a BET specific surface area of ​​1.48 m 2 The pore size was 1.01 μm / g and the average pore size was 23.21 nm. Using this as the positive electrode active material of Example 2, a test cell was produced in the same manner as in Example 1.

[0047] <Example 3> The reaction time for MnSO4 and NiSO4 was 5 hours while stirring. 0.667 Ni 0.333A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was fired at 800° C. The lithium transition metal composite oxide had a BET specific surface area of ​​3.55 m 2 The pore size was 1.0 μm / g and the average pore size was 20.55 nm. Using this as the positive electrode active material of Example 3, a test cell was produced in the same manner as in Example 1.

[0048] <Example 4> The reaction time for MnSO4 and NiSO4 was 8 hours while stirring. 0.667 Ni 0.333 A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was fired at 800° C. The lithium transition metal composite oxide had a BET specific surface area of ​​3.56 m 2 The pore size was 6.73 nm and the average pore diameter was 6.73 nm. Using this as the positive electrode active material of Example 4, a test cell was produced in the same manner as in Example 1.

[0049] <Example 5> Adding a dispersant to the aqueous solution of MnSO4 and NiSO4 and 0.667 Ni 0.333 A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was fired at 800° C. The lithium transition metal composite oxide had a BET specific surface area of ​​3.98 m 2 The pore size was 93.91 nm and the average pore diameter was 93.91 nm. Using this as the positive electrode active material of Example 5, a test cell was produced in the same manner as in Example 1.

[0050] <Comparative Example 1> The reaction time for MnSO4 and NiSO4 was 5 hours while stirring. 0.667 Ni 0.333 A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was fired at 700° C. The lithium transition metal composite oxide had a BET specific surface area of ​​10.77 m 2The pore size was 1.01 μm / g and the average pore diameter was 28.29 nm. Using this as the positive electrode active material of Comparative Example 1, a test cell was produced in the same manner as in Example 1.

[0051] <Comparative Example 2> (M 0.667 Ni 0.333 A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was fired at 700° C. The lithium transition metal composite oxide had a BET specific surface area of ​​14.07 m 2 The pore size was 1.01 μm / g and the average pore diameter was 29.26 nm. Using this as the positive electrode active material of Comparative Example 2, a test cell was produced in the same manner as in Example 1.

[0052] <Comparative Example 3> A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that a dispersant was added to the aqueous solution in which MnSO4 and NiSO4 were dissolved. The amount of the dispersant added was greater than the amount of the dispersant added in Example 5. The lithium transition metal composite oxide had a BET specific surface area of ​​1.29 m 2 The pore size was 1.0 μm / g and the average pore size was 124.71 nm. Using this as the positive electrode active material of Comparative Example 3, a test cell was produced in the same manner as in Example 1.

[0053] <Comparative Example 4> Adding a dispersant to the aqueous solution of MnSO4 and NiSO4 and 0.667 Ni 0.333 A lithium transition metal composite oxide was synthesized in the same manner as in Example 1, except that the mixture of CO3, LiF, and Li2CO3 was sintered at 800°C. The amount of the dispersant added was greater than that added in Example 5. The lithium transition metal composite oxide had a BET specific surface area of ​​3.65 m 2 The pore size was 105.56 nm and the average pore diameter was 105.56 nm. Using this as the positive electrode active material of Comparative Example 4, a test cell was produced in the same manner as in Example 1.

[0054] [Evaluation of the energy density of the positive electrode] The test cells of the examples and comparative examples were charged to 4.7 V at a constant current of 0.1 C in a temperature environment of 25° C., and then discharged to 2.5 V at a constant current of 0.1 C. From the discharge curve at this time, the voltage was calculated by the following formula.

[0055] Voltage = (discharge energy, which is the sum of the electrical quantities at each voltage) / (discharge capacity at 2.5V) The discharge capacity per active material weight when discharged was calculated. The electrode density was calculated from the mass of the positive electrode active material contained in the positive electrode mixture layer. The energy density was calculated by the following formula using the discharge capacity, voltage, and electrode density calculated in this way.

[0056] Energy density (Wh / L) = discharge capacity (Ah / g) × voltage (V) × electrode density (g / cm 3 ) x 1000 The results of the energy density of the positive electrodes of the test cells of the Examples and Comparative Examples are summarized in Table 1. Table 1 also shows the BET specific surface area and average pore diameter of the positive electrode active materials contained in each of the Examples and Comparative Examples.

[0057] [Table 1]

[0058] The test cells of Examples 1-5 had higher energy density than the test cells of Comparative Examples 1-4. [Explanation of symbols]

[0059] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Exterior body 16 Sealing body 17,18 Insulating plate 19 Positive lead 20 Negative lead 21 Grooved part 22 Filters 23 Lower valve body 24 Insulating materials 25 Upper valve 26 Cap 26a opening 27 Gasket

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a lithium transition metal composite oxide, The lithium transition metal composite oxide is General formula Li x Mn y Ni z Me 2-x-y-z O a F b (wherein 1≦x≦1.2, 0.4≦y≦0.7, 0.2≦z≦0.4, 0<b≦0.2, 1.9≦a+b≦2.1, and Me is at least one element selected from Co, Al, Ti, Ge, Nb, Sr, Mg, Si, P, and Sb), BET specific surface area: 1 m 2 / g or more 4m 2 / g or less, A positive electrode active material for a non-aqueous electrolyte secondary battery, the positive electrode active material having an average pore diameter of 100 nm or less.

2. 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal composite oxide has an average pore size of 50 nm or less.

3. The BET specific surface area of ​​the lithium transition metal composite oxide is 3 m 2 / g or more 4m 2 The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein the Mo content is 1 / g or less.

4. 4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein the lithium transition metal composite oxide does not contain Co.

5. A non-aqueous electrolyte secondary battery comprising a positive electrode containing the positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, a negative electrode, and a non-aqueous electrolyte.

Citation Information

Patent Citations

  • Lithium compound oxide particle for lithium secondary battery positive electrode material, and lithium secondary battery positive electrode using the same, and the lithium secondary battery

    JP2005123179A

  • Positive electrode active material for lithium secondary battery, positive electrode and secondary battery

    JP2015018678A

  • Positive electrode active material for lithium secondary batteries, electrode for lithium secondary batteries, and lithium secondary battery

    JP2015099646A

  • Electrode, battery, battery pack, vehicle, power storage system, electric tool, and electronic equipment

    WO2019031380A1